2017
DOI: 10.1519/jsc.0000000000001489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short or Long Warm-up on Intermediate Running Performance

Abstract: van den Tillaar, R, Vatten, T, and von Heimburg, E. Effects of short or long warm-up on intermediate running performance. J Strength Cond Res 31(1): 37-44, 2017-The aim of the study was to compare the effects of a long warm-up (general + specific) and a short warm-up (specific) on intermediate running performance (3-minute run). Thirteen experienced endurance-trained athletes (age 23.2 ± 2.3 years, body mass 79.8 ± 8.2 kg, body height 1.82 ± 0.05 m) conducted 2 types of warm-ups in a crossover design with 1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…The first 40-m effort was at a self-estimated intensity of approximately 60% of estimated maximal sprinting velocity; each 40-m effort thereafter increased by approximately 5% until they reached 95% of maximal self-estimated intensity. In each rest period, one of seven dynamic flexibility exercises for the shoulders, hip, knee, and ankle joints was completed, starting with the shoulders and working downwards to increase the range of motion of the different joints, as described in detail by van den Tillaar et al [23] and van den Tillaar and von Heimburg [24]. After the warm-up, the participants had 5 minutes of active rest (easy walking and standing) before they performed one of the three protocols.…”
Section: Methodsmentioning
confidence: 99%
“…The first 40-m effort was at a self-estimated intensity of approximately 60% of estimated maximal sprinting velocity; each 40-m effort thereafter increased by approximately 5% until they reached 95% of maximal self-estimated intensity. In each rest period, one of seven dynamic flexibility exercises for the shoulders, hip, knee, and ankle joints was completed, starting with the shoulders and working downwards to increase the range of motion of the different joints, as described in detail by van den Tillaar et al [23] and van den Tillaar and von Heimburg [24]. After the warm-up, the participants had 5 minutes of active rest (easy walking and standing) before they performed one of the three protocols.…”
Section: Methodsmentioning
confidence: 99%
“…A number of recent studies have shown NMTs to be a practical, valid, and reliable tool for assessing a range of clinical (Janaudis-Ferreira et al, 2010 ) and sport-specific movement patterns; including sprinting (Gonzalez et al, 2013 ; Mangine et al, 2014 ), endurance (Davies et al, 1984 ; Stevens et al, 2014 , 2015 ; Morgan et al, 2016 ; Waldman et al, 2017 ) and team-sport running (Sirotic and Coutts, 2008 ; Aldous et al, 2014 ; Tofari et al, 2015 ). Consequently, the last few years has seen a marked increase in the use of NMTs in laboratory based interventions investigating the impact of environmental factors (Aldous et al, 2016 ; Gerrett et al, 2016 ; Sweeting et al, 2017 ; Stevens et al, 2017a , b ), warm up (van den Tillaar et al, 2017 ), recovery (Pelka et al, 2017 ), fatigue (Tofari et al, 2017 ), and ergogenic aids (Sear et al, 2010 ; Coull et al, 2015 ) on performance. However, it is still unclear how the cardiometabolic demands of running on a non- NMT compare with that of running either overground or on a MOT.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados do presente estudo corroboram os resultados de estudo prévios [13,17] que investigaram diferentes estratégias de aquecimento. Zourdos et al [13] avaliaram 16 corredores de longa distância de elite, submetidos a dois protocolos com duração de 13 minutos antes da corrida de teste.…”
Section: Discussionunclassified